2018
DOI: 10.5114/reum.2018.79500
|View full text |Cite
|
Sign up to set email alerts
|

Median neuropathy at the wrist in patients with systemic sclerosis: two-year follow-up study

Abstract: ObjectivesTo determine the incidence and factors associated with median neuropathy at the wrist (MNW) in systemic sclerosis (SSc) patients using an electrodiagnostic (EDX) study.Material and methodsSSc patients who attended the scleroderma clinic, Srinagarind Hospital, were prospectively evaluated by questionnaire, physical examination, and EDX study. The questionnaire consisted of the baseline characteristics, type of scleroderma, clinical signs and symptoms associated with scleroderma, and the Boston questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We performed this measurement because we hypothesize that increased skin thickness may increase compression and decrease carpal tunnel compliance. In the literature, studies show that increased skin thickness due to fibrosis of the skin in scleroderma patients causes median nerve neuropathy due to mechanical compression of the median nerve [30][31][32] . Based on these studies, we evaluated the relationship…”
Section: Discussionmentioning
confidence: 99%
“…We performed this measurement because we hypothesize that increased skin thickness may increase compression and decrease carpal tunnel compliance. In the literature, studies show that increased skin thickness due to fibrosis of the skin in scleroderma patients causes median nerve neuropathy due to mechanical compression of the median nerve [30][31][32] . Based on these studies, we evaluated the relationship…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review from Turkey concluded that trigeminal neuropathy (TN) (16.5%), peripheral sensorimotor polyneuropathy (14.3%), and carpal tunnel syndrome (CTS) (6.6%) were the most frequent forms of PN-SSc [29], and individual cases of TN in SSc were mainly reported in the last 5 years. In the studies by Yagci et al [29] and Sriwong PT et al [30], the prevalence of median neuropathy in SSc was about 35%. Most CTS in patients with SSc were asymptomatic.…”
Section: Systemic Sclerosis (Ssc) or Sclerodermamentioning
confidence: 94%
“…In regard to PNs, in a cross-sectional study by Raja et al ( 73 ) and Paik et al ( 74 ), the prevalence of PN in SSc varied from 28 to 36.6%. In a recent systematic review from AlMehmadi et al ( 75 ), compression neuropathies were reported in 26.5% of the studies, and according to Yagci et al ( 76 ) and Sriwong et al ( 77 ), the prevalence of median neuropathy in SSc is estimated to be 35%. Most CTS in patients with SSc were asymptomatic.…”
Section: Neuropathies In the Most Common Acquired Rheumatological Con...mentioning
confidence: 99%
“…Calcinosis cutis and, less commonly, soft tissue thickening, resulted in the main risk factor for compression neuropathies in SSc ( Figure 7 ). Risk factors for non-compression neuropathies include advanced diffuse diseases, anti-centromere antibodies, presence of vasculitis, iron deficiency with anemia, drugs such as metoclopramide and pembrolizumab, silicosis, and uremia ( 77 ). Autonomic nervous systems, especially cardiac autonomic functions, may also be altered in SSc ( 78 ).…”
Section: Neuropathies In the Most Common Acquired Rheumatological Con...mentioning
confidence: 99%